DETECTION OF RNA VIRUSES FROM INFLUENZA AND HIV TO EBOLA AND SARS-COV-2: A REVIEW - Bukasov, Rostislav; Dossym, Dina; Filchakova, Olena (Analytical Methods, 2020)
RNA-based viruses likely make up the highest pandemic threat among all known pathogens in about the last 100 years, since the Spanish Flu of 1918 with 50 M deaths up to COVID-19. Nowadays, an efficient and affordable testing strategy for such viruses have become the paramount target for the fields of virology and bioanalytical chemistry. The detection of the viruses (influenza, hepatitis, HIV, Zika, SARS, Ebola, SARS-CoV-2, etc.) and human antibodies to these viruses is described and tabulated in terms of the reported methods of detection, time to results, accuracy and specificity, if they are reported. ...